Arm Holding PLC : ecosystem advantage - Williamson, Peter J.; De Meyer, Amoud; Muthirulan, Arun ([London] : SAGE, 2016)
This case explores how ARM has nurtured the creation of a business ecosystem comprising a large network of different types of partners to develop competitive advantage in the semiconductor industry between 1990 and 2009 and become a leading global player whose IP lies at the core of 95% of mobile phones produced in the world. The case enables students to compare and contrast this ecosystem strategy with the alternative, vertically integrated business model adopted by Intel.
Originally Published in: Williamson, P., De Meyer, A., & Muthirulan, A. (2009). ARM Holding Plc: Ecosystem Advantage. Cambridge: University of Cambridge Judge Business School.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; ARM Holding (Firm); Knowledge management -- Case studies; Competition -- Case studies; Strategic planning -- Case studies